Predisposing Factors of Atrial High-rate Episodes in Patients with Permanent Pacemaker Implantation in Central Chest Institute of Thailand - Auitrakarn, Suriya; Assavahanrit, Jarin; Methavigul, Komsing (Journal of The Department of Medical Services, 2024)
Background: The atrial high-rate episodes (AHREs) are considered clinically correlated with atrial fibrillation (AF). Moreover, the stroke risk is increasing following the AHREs burden and/or CHA2 DS2 -VASc score. However, the predisposing factors of the AHREs were not clearly known. Objective: To investigate the predisposing factors of AHREs in patients with dual-chamber pacemakers. Method: This study was a retrospective observational study recruiting patients without history of AF prior to the dual-chamber pacemaker implantation. Patients with evidences of other atrial tachyarrhythmias prior to the dual-chamber pacemaker implantation were excluded. The baseline demographic data, past medical history, medications, echocardiographic parameters, electrocardiographic findings and pacemaker interrogation data were analyzed and compared between patients with and without AHREs. Predisposing factors predicting AHREs was analyzed by using univariate and multivariate logistic regression analysis. Result: A total of 239 patients undergoing dual-chamber pacemaker implantation in Central Chest Institute of Thailand among January 2017 to December 2021 were recruited. The data of 117 patients from 239 patients were analyzed. There were 89 patients had no AHREs and 28 patients had AHREs. Multivariate logistic regression analysis showed that the percentage of atrial pacing was significantly greater in patients with AHREs (odds ratio 1.02; 95% CI 1.003 to 1.041; p-value = .021). Conclusion: Increased atrial pacing was the only predisposing factor of AHREs in Thai patients with permanent pacemaker. However, larger prospective study should be studied in the future.